NILAI BUDAYA DALAM LEKSIKON PENDULANGAN INTAN PADA MASYARAKAT BANJAR: KAJIAN ETNOLINGUISTIK - Yuliati Puspita Sari (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2019)
This study aims to (1) classify several terms in diamond mining lexicon in Banjar community; (2) describe cultural value in diamond mining lexicon in Banjar community. The data in this study are various form of terms related to diamond mining culture in the Banjar community. The method used in this study is qualitative method. The results shows that based on its form, the terms in diamond mining lexicon can be classified from the using of the tools, the application of the techniques, and the designation of the people involved in diamond mining. Meanwhile, the universal cultural values that emerge in diamond mining lexicon are  the harmonization with the environment, the awareness at work, creative, persistence, and the spirit of mutual cooperation. Those cultural values are formed from the results of interactions between humans, and interactions between humans and nature.